Betula pendula Roth. survival and growth in treeline is affected by genotype and environment - Kari Saikkonen; Otto Saikkonen; Marjo Helander; Irma Saloniemi (Scientific Reports)
Abstract Alpine and Arctic treelines are assumed to be shifting toward higher latitudes and altitudes as a consequence of climate warming. Here, we compared the survival and growth of 1264 silver birch (Betula pendula Roth.) trees representing nine half-sib families. The trees were planted in two arboreta situated in distinct altitudinal environments in northern Finland in 1976 and 1977. The arboreta were located 9 km from each other and approximately 60 km north from the species’ most northern natural growth site at that time. They were fenced to prevent vertebrate grazing, which is known to be among the most important factors limiting the expansion and regeneration of forests in European treeline ecotones. Overall, 90% and 81% of the trees were alive five and 40 years after planting in the two arboreta, respectively. Survival of trees varied among the half-sib families, especially in Arboretum 1, situated in a lower altitudinal environment characterized by soils with lower levels of nutrients, a longer growing season, and harsher winter temperatures. Trees were distinctively bigger in Arboretum 2: 50% taller (6.2 m vs. 4.4 m) and 68% thicker (9.5 cm vs. 5.6 cm) compared to trees in Arboretum 1. Furthermore, the performance of half-sib families varied depending on the garden they were grown in. These results demonstrate that the acclimation capacity of B. pendula allows its distribution to expand north from the present range; however, local abiotic environmental conditions (soil fertility and winter temperatures) and other selection pressures (herbivory) are likely to affect the genetic structure and growth of B. pendula populations.